SAT0563 Long Term Improvements in Physical Function are Associated with Improvements in Dactylitis, Enthesitis, Tender and Swollen Joint Counts, and Psoriasis Skin Involvement: Results from a Phase 3 Study of Ustekinumab in Psoriatic Arthritis Patients. (9th June 2015) - Kavanaugh, A.; Puig, L.; Gottlieb, A.B.; Ritchlin, C.; Li, S.; You, Y.; Mendelsohn, A.M.; Song, M.; Rahman, P.; McInnes, I.
Abstract : Objectives: To evaluate the association of improvements in tender and swollen joint counts (TJC, SJC), psoriasis skin involvement, and dactylitis/enthesitis (in patients affected at baseline) with improvement in physical function using data from the ustekinumab (UST) PSUMMIT 1 trial in psoriatic arthritis (PsA) pts. Methods: Adult PsA pts (n=615) with active disease (≥5 SJC and ≥5 TJC; CRP ≥0.3 mg/dL) despite DMARD and/or NSAIDs were randomized to UST45mg, 90mg, or PBO at wks 0, 4, and q12wks. Pts treated with prior anti-TNF agents were excluded. Stable concomitant MTX was permitted but not mandated. At wk16, pts with <5% improvement in TJC and SJC entered blinded early escape (PBO→UST45mg; UST45mg→90mg; 90mg→90mg). PBO-treated patients subsequently crossed over to UST45mg at wk24. Pts received q12wks dosing to wk88, with final efficacy evaluation at wk100 and safety assessment at wk108. The percent change from baseline in enthesitis score, dactylitis score, TJC and SJC by HAQ responder status (response defined as achieving ≥0.3 point improvement from baseline) was assessed at wks 52 and 100.The correlation between change from baseline in HAQ and percent change from baseline in TJC, SJC, enthesitis and dactylitis were also determined at wks 52 and 100. Results: At baseline, mean (median) TJC and SJC values were 23.5 (20.0) and 13.5 (10.0), respectively. 441 (71.7%) and 296 (48.1%) patients had enthesitis or dactylits at baseline, respectively; 440 (71.7%) patients had >3% BSA psoriasis skin involvement. Improvements in TJC, SJC, dactylitis and enthesitis, and PASI scores were generally greater in HAQ responders compared with HAQ non-responders at both wk52 and wk100 (Table ). Significant correlations were demonstrated between the HAQ change from baseline with percent change in outcomes parameters for all outcomes (Table ) at wk52 and wk100. In addition, associations were observed at earlier time points at wk24/wk28 [TJC -0.39/-0.36; SJC -0.27/-0.20; enthesitis 0.30/0.28 (all p<0.0001); dactylitis 0.19/0.18 (p=0.001/p=0.002); PASI -0.24/-0.10 (p<0.0001/p=0.0397)]. Conclusions: Based on this post-hoc analysis of the PSUMMIT 1 population, improvements in physical function as measured by HAQ were associated with improvements in TJC, SJC, dactylitis and enthesitis, and these correlations were observed as early as week 24 and continued through week100. Improvement in skin disease was also associated with improvements in HAQ. Disclosure of Interest: A. Kavanaugh Grant/research support from: AbbVie, Amgen, Janssen, and UCB., L. Puig Grant/research support from: AbbVie, Amgen, Boehringer, Celgene, Eli Lilly, Janssen, Leo-Pharma, Merck/Schering-Plough, Merck-Serono, Novartis, Pfizer, Sandoz, and VBL, A. Gottlieb Grant/research support from: Amgen, AbbVie, Celgene, Coronado, Eli Lilly, Janssen, Levia, Merck, and Pfizer., Consultant for: AbbVie, Actelion, Akros, Amgen, Astellas, Bristol Myers Squibb, Canfite, Catabasis, Celegene, CSL Behring Biotherapies for Life, Coronado, Dermipsor, Eli Lilly, GlaxoSmithKline, Incyte, Janssen, Karyopharm, Novartis, Novo Nordisk, Pfizer, Sanofi Aventix, UCB, Vertex, and Xenoport., C. Ritchlin Grant/research support from: Amgen, Janssen, and UCB, Consultant for: AbbVie, Amgen, Janssen, Regeneron, Roche, and UCB., S. Li Employee of: Janssen R&D, LLC., Y. You Employee of: Janssen R&D, LLC., A. Mendelsohn Employee of: Janssen R&D, LLC., M. Song Employee of: Janssen R&D, LLC., P. Rahman Grant/research support from: AbbVie, Amgen, Janssen, Pfizer, and Novartis., I. McInnes Grant/research support from: AbbVie, BMS, Janssen, Pfizer, Roche, Merck/Schering-Plough, and UCB